Análise de falhas dos equipamentos de um alto forno - Belo, Eduardo de Oliveira (2019)
With the global competitiveness increasing in the steel industry and large-scale production by large countries such as China and USA, it is necessary to reduce costs in a smart and strategical manner in order to stabilize the production. To achieve these metrics of growth and productivity, efficiency in the execution of maintenance applied to the production is indispensable. If predictive, preventive and corrective maintenance is planned and executed correctly, the number of equipment failures tends to decrease significantly, increasing asset reliability and availability, which will in return, help maximize the results while simultaneously minimizing costs. Due to various occurrences of equipment failure in the blast furnace in 2018 and constant loss of production, it will be applied in this study the RCM method (Reliability Centered Maintenance) to better analyze how the maintenance is performed with the objective of reducing the asset failure rate.